Reaksi Pasar Modal terhadap Peristiwa Sebelum dan Sesudah Pengumuman Boikot Produk Pro Israel - Novita, Fitria Indah; Cheisviyanny, Charoline (Universitas Negeri Padang, 2024)
This study aims to analyze changes in abnormal returns and trading volume activity (TVA) before and after the announcement of MUI Fatwa Number 83 of 2023 with a focus on the response of the global community which can be reflected in a boycott of products affiliated with Israel. This research falls into the type of event study with the Population is a company listed on the Indonesia Stock Exchange and affected by the boycott of Israel as many as 11 companies with a span of 30 days before the event and 30 days after the event. by using purposive sampling method. The use of Paired Sample T-test in this study resulted in the conclusion that abnormal returns and trading volume activity (TVA) before and after the issuance of MUI Fatwa No. 83 of 2023 are not significantly different. Although the conflict and the fatwa caused a high level of uncertainty, this finding reflects that investors still maintain a high interest in investing in the capital market. The implications of this research can serve as a foundation for designing more adaptive investment strategies in the era of global geopolitics.